Degradation of emerging contaminants using Co/Nb-modified SnO2 nanoparticles and produced with babassu mesocarp (Orbgnya Speciosa) - Lima, Juliana B.; Marques, Gleison N.; Ferreira, Davi S.; Moreira, Ailton.J. [UNESP]; Assis, Marcelo; Longo, Elson; Bernardi, Maria Inês B.; Rangel, José H.G.; Azevedo, Emilio; Mascaro, Lucia H.; Oliveira, Marcelo M. (Elsevier, 2025)
In this work, pure SnO2 nanoparticles (SnO2 NPs), doped and co-doped with Co2 + and Nb5+ (0.05 and 0.1 mol), were prepared using babassu mesocarp (Orbgnya Speciosa) extract as a natural polymerizing agent and microwave-assisted hydrothermal treatment. X-ray diffraction analysis (XRD) showed that the crystallinity of the NPs increases by more than 20 % in the presence of babassu mesocarp, and the particle size decreases from 260.50 nm to 18.88 nm even with doping Co2+/Nb5+. The photocatalytic activity under UV irradiation for the degradation of the rhodamine b (RhB) dye showed that the NPs produced with the mesocarp achieved a degradation of up to 90 % and 97 % of RhB. The Co2+ doped samples were evaluated for their ability to degrade emerging contaminants such as Ofloxacin (OFX) and Diclofenac Sodium (DCF) in domestic wastewater. The assays showed that even in the presence of natural organic matter, the catalysts efficiently absorbed UV-C light to produce the oxidizing species consumed in the degradation of organic contaminants. This antibiotic showed high resistance to photolysis but degraded up to 94 %. The degradation of DCF is > 95 %. Thus, this study brings new approaches to producing efficient photocatalysts to degrade emerging contaminants in domestic wastewater.
Keywords: Babassu coconut mesocarp; Emerging contaminants; Green synthesis; Photocatalysis; Tin dioxide